Variability in the management and outcomes of extremely preterm births across five European countries: a population-based cohort study. Issue 5 (23rd February 2017) - Smith, Lucy K; Blondel, Beatrice; Van Reempts, Patrick; Draper, Elizabeth S; Manktelow, Bradley N; Barros, Henrique; Cuttini, Marina; Zeitlin, Jennifer
Abstract : Objective: To explore international variations in the management and survival of extremely low gestational age and birthweight births. Design: Area-based prospective cohort of births Setting: 12 regions across Belgium, France, Italy, Portugal and the UK Participants: 1449 live births and fetal deaths between 22 +0 and 25 +6 weeks gestation born in 2011–2012. Main outcome measures: Percentage of births; recorded live born; provided antenatal steroids or respiratory support; surviving to discharge (with/without severe morbidities). Results: The percentage of births recorded as live born was consistently low at 22 weeks and consistently high at 25 weeks but varied internationally at 23 weeks for those weighing 500 g and over (range 33%–70%) and at 24 weeks for those under 500 g (range 5%–71%). Antenatal steroids and provision of respiratory support at 22–24 weeks gestation varied between countries, but were consistently high for babies born at 25 weeks. Survival to discharge was universally poor at 22 weeks gestation (0%) and at any gestation with birth weight <500 g, irrespective of treatment provision. In contrast, births at 23 and 24 weeks weighing 500 g and over showed significant international variation in survival (23 weeks: range: 0%–25%; 24 weeks range: 21%–50%), reflecting levels of treatment provision. Conclusions: Wide international variation exists in the management and survival of extremely preterm births at 22–24 weeks gestation. Universally poor outcomes for babies at 22 weeks and for those weighing under 500 g suggest little impact of intervention and support the inclusion of birth weight along with gestational age in ethical decision-making guidelines.